Yersinia pseudotuberculosis-derived adhesins - A. A. Byvalov; I. V. Konyshev (Инфекция и иммунитет, 2019)
Around fifteen surface components referred to adhesins have been identified in Yersinia pseudotuberculosis combining primarily microbiological, molecular and genetic, as well as immunochemical and biophysical methods. Y. pseudotuberculosis-derived adhesins vary in structure and chemical composition but they are mainly presented by protein molecules. Some of them were shown to participate not only in adhesive but in other pathogen-related physiological functions in the host-parasite interplay. Adhesins can mediate bacterial adhesion to eukaryotic cell either directly or via the extracellular matrix components. These adhesion molecules are encoded by chromosomal DNA excepting YadA protein which gene is located in the calcium-dependence plasmid pYV common for pathogenic yersisniae. An optimum temperature for adhesin biosynthesis is located close to the body temperature of warm-blooded animals; however, at low temperature only invasin InvA, full-length smooth lipopolysaccharide and porin OmpF are produced in Y. pseudotuberculosis. Several adhesins (Psa, InvA) can be expressed at low pH (corresponds to intracellular content), thereby defining pathogenic yersiniae as facultative intracellular parasites. Three human Yersinia genus pathogens differ by ability to produce adhesins. Y. pseudotuberculosis adherence to host cells or extracellular matrix components is determined by a cumulative adhesion-based activity, which expression depends on chemical composition and physicochemical environmental conditions. It’s proposed that at the initial stage of infectious process adherence of Y. pseudotuberculosis to intestinal epithelium is mediated by InvA protein and “smooth” LPS form. These adhesins are produced in bacterial cells at low (lower than 30°С) temperature occurring in environment from which a pathogen invades into the host. At later stages of pathogenesis, after penetrating through intestinal epithelium, bacterial cells produce other adhesins, which promote survival and dissemination primarily into the mesenteric lymph nodes and, possibly, liver and spleen. At later stages of pathogenesis, after penetrating through intestinal epithelium, bacterial cells produce other adhesins, which promote survival and dissemination primarily into the mesenteric lymph nodes and, perhaps, liver and spleen. Qualitative and quantitative spectrum of Y. pseudotuberculosis adhesins is determined by environmental parameters (intercellular space, intracellular content within the diverse eukaryotic cells).